Economics an Introduction - Villegas, Bernardo M.; Abola, Victor A. (Manila, 2009)
This book continues its tradition of providing college students with the basic principles of economics through the Macroeconomy or Economics of a Nation. As in previous editions, the book seeks to blend modern economic theory with Philippine facts and issues, making the learning process easier and more relevant. It also puts a clear development orientation to an introductory course, by tackling growth and developmental issues through most of the book.
Keywords: Economics